Automation of the procedure for determining the admissibility of erosion- corrosion wear in pipelines of nuclear power plants made of carbon steels - Hryhoriy Vorona; Mykyta Ananchenko; Oleh Makhnenko (Mechanics and Advanced Technologies)
Many pipelines in Ukrainian nuclear power plants have been in operation for over 30 years, and the determination of the admissibility of erosion-corrosion wear (ECW) defects in the pipeline wall metal is currently one of the pressing issues in the nuclear energy sector of Ukraine. A comparative analysis of determining the admissibility of pipe wall thinning due to ECW was conducted using the adopted methodology “MT-T.0.03.224-18” by the State Enterprise “Energoatom” and the guidance based on the use of regulatory documents for designing pipeline elements. The use of the methodology demonstrated significant advantages in terms of reducing the conservatism of ECW assessment, especially for small-scale thinning and pipelines operating at pressures below 60-80 kgf/cm2, which allows for a substantial reduction in repair work. However, the implementation of the methodology in practice may encounter difficulties due to the complexity and labor-intensiveness of the calculation assessment procedure for nuclear power plant personnel. Therefore, to automate the ECW admissibility assessment in accordance with the methodology requirements, software (SW) was developed for use by nuclear power plant personnel, enabling the prompt generation of a protocol for the express assessment procedure of ECW admissibility for a straight section of the pipeline based on the measurement results of wall thinning parameters in the axial direction. The software allows for concluding whether the section can be put into operation, sent for repair, or requires further refined assessment. Additionally, software based on the finite element method (FEM) was developed, which, when necessary, allows for a refined assessment of a straight section, taking into account the depth and angle of thinning in the circumferential direction, and calculates the stress of the limit plastic state of the pipeline section with ECW from the perspective of viscous fracture. The devel- opment is applicable in the field of nuclear energy in Ukraine.